(untitled) (KULT_online, 2025)
Whitney Barlow Robles’ Curious Species advances a compelling counter-narrative to existing understandings of the emergence of natural history by foregrounding the agency of animals. Combining original research with first-person nature writing, the author contends that raccoons, rattlesnakes, and flounders all had a hand – or a tail, or a fin – in shaping and frustrating the attempts of naturalists to grasp the natural world. But to what extent were these and other Curious Species exceptions to the imperial rule which dominated nature in the 18th century?